Pengelolaan Pendidikan Islam yang Efektif: Menjawab Tantangan Pendidikan Islam di Era Industri 4.0 - Eriyanto Eriyanto (Jurnal Pendidikan Islam Indonesia, 2019)
The effective madrasah management refers to the good management of madrasah with the appropriate teaching and learning processes conforming to the needs of students with high learning outcomes and motivation. The effective madrasah management has as a system includes many aspects of input, process, output, and outcome as well as the madrasah’s order. They can support one another to achieve the vision, mission, and objectives of madrasah that managed effectively and efficiently.